Heritable gene expression differences between apomictic clone members in Taraxacum officinale: Insights into early stages of evolutionary divergence in asexual plants. (December 2016) - Ferreira de Carvalho, Julie; Oplaat, Carla; Pappas, Nikolaos; Derks, Martijn; de Ridder, Dick; Verhoeven, Koen
Abstract Background Asexual reproduction has the potential to enhance deleterious mutation accumulation and to constrain adaptive evolution. One source of mutations that can be especially relevant in recent asexuals is activity of transposable elements (TEs), which may have experienced selection for high transposition rates in sexual ancestor populations. Predictions of genomic divergence under asexual reproduction therefore likely include a large contribution of transposable elements but limited adaptive divergence. For plants empirical insight into genome divergence under asexual reproduction remains limited. Here, we characterize expression divergence between clone members of a single apomictic lineage of the common dandelion (Taraxacum officinale ) to contribute to our knowledge of genome evolution under asexuality. Results Using RNA-Seq, we show that about one third of heritable divergence within the apomictic lineage is driven by TEs and TE-related gene activity. In addition, we identify non-random transcriptional differences in pathways related to acyl-lipid and abscisic acid metabolisms which might reflect functional divergence within the apomictic lineage. We analyze SNPs in the transcriptome to assess genetic divergence between the apomictic clone members and reveal that heritable expression differences between the accessions are not explained simply by genome-wide genetic divergence. Conclusion The present study depicts a first effort towards a more complete understanding of apomictic plant genome evolution. We identify abundant TE activity and ecologically relevant functional genes and pathways affecting heritable within-lineage expression divergence. These findings offer valuable resources for future work looking at epigenetic silencing andCis -regulation of gene expression with particular emphasis on the effects of TE activity on asexual species' genome.